Entomopathogenic Nematodes (Nematoda: Rhabditida: families Steinernematidae and Heterorhabditidae) - Nastaran Tofangsazie; Steven P. Arthurs; Robin M. Giblin-Davis (EDIS)
Entomopathogenic nematodes are soft bodied, non-segmented roundworms that are obligate or sometimes facultative parasites of insects. They occur naturally in soil environments and locate their host in response to carbon dioxide, vibration, and other chemical cues. They fit nicely into integrated pest management programs because they are nontoxic to humans, specific to their target pests, and can be applied with standard pesticide equipment. This 4-page fact sheet was written by Nastaran Tofangsazie, Steven P. Arthurs, and Robin M. Giblin-Davis, and published by the UF Department of Entomology and Nematology, August 2012.